2019
DOI: 10.1007/s11368-019-02492-3
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the concentrations of PCDDs/Fs in contaminated bottom sediments and their sources and ecological risk

Abstract: Purpose The purpose of the study was to determine the levels of polychlorinated dibenzo-p-dioxin and polychlorinated dibenzofuran (PCDD/F), two types of persistent organic pollutant (POP), in an urban retention reservoir located in an industrial zone within a coal-mining region. It also assesses the potential ecological risk of the PCDDs/Fs present in bottom sediments and the relationship between their content and the fraction of organic matter. Materials and methods The sediment samples were collected from Ry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Besides organic matter, the clay and silt fractions of sediments play an important role in the distribution of dioxins in bottom sediments (Zhang et al 2010;Li et al 2012). In our previous study, fine fractions of sediments were demonstrated to play a dominant role in the distribution of dioxins in Rybnik Reservoir (Baran et al 2019c). Vácha et al (2011) and Lee et al (2006) also observed a poor relation between the concentration of organic pollutants and the content of TOC in the sediment.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Besides organic matter, the clay and silt fractions of sediments play an important role in the distribution of dioxins in bottom sediments (Zhang et al 2010;Li et al 2012). In our previous study, fine fractions of sediments were demonstrated to play a dominant role in the distribution of dioxins in Rybnik Reservoir (Baran et al 2019c). Vácha et al (2011) and Lee et al (2006) also observed a poor relation between the concentration of organic pollutants and the content of TOC in the sediment.…”
Section: Discussionmentioning
confidence: 80%
“…It encloses a small catchment area, which is highly urbanised and strongly influenced by heavy industry (Baran et al 2019a ). In our previous studies, the concentration of PCDDs/Fs in the sediments form Rybnik reservoir ranged from 1.65 to 32.68 pg TEQ g −1 (Baran et al 2020 ). Morover, we found that PCDD/F concentrations in the sediments were 2–38-fold higher than the Sediment Quality Guidelines limit, indicating high ecological risk potential.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Humic substances are capable of ionic, donor-acceptor, and hydrophobic bonding. Therefore, they can bind POPs in non-toxic and nonbioavailable humic complexes [ 27 ]. The higher the soil pH, the lower the PCBs content is in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…3 Sediment quality guidance, sediment quality assessment Baran et al (2019) present a study that assessed the levels of persistent organic contaminants such as polychlorinated dibenz-p-dioxin and polychlorinated dibenzofuran (PCDD/Fs) in lake sediments of the coal mining and highly industrial region in Poland. PCDD/F concentrations in the sediment samples were 2-to 38-fold higher than the sediment quality guidelines limits, indicating high ecological risk potential.…”
Section: Sediment Management and Sediment Policymentioning
confidence: 99%